Enhancing deep visible-light photoelectrocatalysis with a single solid-state synthesis: Carbon nitride/TiO2 heterointerface - Silva, Ingrid F.; Pulignani, Carolina; Odutola, Jokotadeola; Galushchinskiy, Alexey; Texeira, Ivo F.; Isaacs, Mark; Mesa, Camilo A.; Scoppola, Ernesto; These, Albert; Badamdorj, Bolortuya; Ángel Muñoz-Márquez, Miguel; Zizak, Ivo; et al. (Journal of Colloid and Interface Science, 2025)
Visible-light responsive, stable, and abundant absorbers are required for the rapid integration of green, clean, and renewable technologies in a circular economy. Photoactive solid–solid heterojunctions enable multiple charge pathways, inhibiting recombination through efficient charge transfer across the interface. This study spotlights the physico-chemical synergy between titanium dioxide (TiO2) anatase and carbon nitride (CN) to form a hybrid material. The CN(10%)-TiO2(90%) hybrid outperforms TiO2 and CN references and literature homologs in four photo and photoelectrocatalytic reactions. CN-TiO2 achieved a four-fold increase in benzylamine conversion, with photooxidation conversion rates of 51, 97, and 100 % at 625, 535, and 465 nm, respectively. The associated energy transfer mechanism was elucidated. In photoelectrochemistry, CN-TiO2 exhibited 23 % photoactivity of the full-spectrum measurement when using a 410 nm filter. Our findings demonstrate that CN-TiO2 displayed a band gap of 2.9 eV, evidencing TiO2 photosensitization attributed to enhanced charge transfer at the heterointerface boundaries via staggered heterojunction type II.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Benzylamine photooxidation; CN-TiO; Heterointerface; Hydrogen production; TiO